Prevalence of airflow obstruction in patients with stable systolic heart failure. Issue 1 (December 2017) - Dalsgaard, Morten; Plesner, Louis; Schou, Morten; Kjøller, Erik; Vestbo, Jørgen; Iversen, Kasper
Abstract Background Chronic obstructive pulmonary disease (COPD) is an important differential diagnosis in heart failure (HF). However, routine use of spirometry in outpatient HF clinics is not implemented. The aim of the present study was to determine the prevalence of both airflow obstruction and non obstructive lung function impairment in patients with HF and to examine the effect of optimal medical treatment for HF on lung function parameters. Methods Consecutive patients with HF (ejection fraction (EF) < 45%) and New York Heart Association (NYHA) functional class II-IV at 10 different outpatient heart failure clinics were examined with spirometry at their first visit and after optimal medical treatment for HF was achieved. airflow obstruction was classified and graded according to the GOLD 2011 revision. Results Baseline spirometry was performed in 593 included patients and 71 (12%) had a clinical diagnosis of COPD. Mean age was 69 ± 11 years and mean EF was 30 ± 9%. Thirty-two % of the patients were active smokers and 53% were previous smokers. Mean FEV1 and FVC was 77.9 ± 1.7% and 85.4 ± 1.5% of predicted respectively. Obstructive pattern was observed in 233 (39%) of the patients. Of these, 53 patients (9%) had mild disease (GOLD I) and 180 (30%) patients had moderate to very severe disease (GOLD II-IV). No difference in spirometric variables was observed following up titration of medication. Conclusion In stable patients with HF airflow obstruction is frequent and severely underdiagnosed. Spirometry should be considered in all patients with HF in order to improve diagnosis and treatment for concomitant pulmonary disease.